Evaluation of Dynamic Postural Balance in Pediatric Familial Mediterranean Fever Patients - Resul Yılmaz; Ahmet İnanır; Nafia Özlem Kazancı; Nurşen Çakan; Ali Gül (Galenos Yayinevi, 2018)
Aim:Familial Mediterranean Fever (FMF) is an autoinflammatory and chronic disorder. Colchicine has been prescribed to treat FMF since 1972. Balance is a complex function of the neuromuscular system. The aim of this study is to determine 1) if there is a connection between FMF and dynamic balance, 2) if colchicine use affects balance, and 3) if the disease severity score is related to a disruption in balance.Materials and Methods:The study examined 50 pediatric patients with FMF and 130 healthy age- and sex-matched children as control subjects. Dynamic postural stability was measured using the Biodex Stability System (BSS).Results:The stability indices were significantly higher in the FMF group than in the controls. There was no relationship between the FMF disease severity score and the three stability indices, while the colchicine dose was related to all three stability indices.Conclusion:By detecting any change in balance status early using a simple, safe, objective measurement of balance via the BSS in FMF patients, neuromyopathy could be identified earlier and unwanted outcomes prevented.